IDENTIFIKASI DAN PEMETAAN KUALITAS AIRTANAH DANGKAL DI SEKITAR DAERAH INDUSTRI TAHU, KECAMATAN MANDAU, DURI - fauzia, sifa; Mairizki, Fitri (Journal of Research and Education Chemistry, 2025)
Mandau District is located in the city of Duri, Riau Province, and is an area experiencing rapid economic growth based on household-scale industries. One of the growing micro-enterprises is the tofu industry, which generates liquid waste. The liquid waste from the tofu industry is characterized by a high content of organic matter, COD, and total nitrogen (Ntotal), which, if not properly treated, can seep into the ground and contaminate the groundwater layer. The aim of this study is to analyze the physical and chemical quality of groundwater and assess its feasibility as a source of drinking water. The method used in this research involves field sampling of groundwater using purposive sampling, followed by laboratory analysis. The parameters tested include color, taste, odor, TDS, EC, pH, COD, and Ntotal. The results of the physical and chemical analysis of groundwater at 20 stations in the study area show that all stations (100%) have clear water; all stations (100%) have tasteless groundwater; 19 stations (95%) have odorless groundwater and 1 station (5%) has odorous groundwater; all stations (100%) have TDS values < 500 mg/l; EC values range from 31 to 280 µS/cm; pH values range from 7,69 - 7,83; 19 stations (95%) have COD values < 10 mg/l and 1 station (5%) has COD > 10 mg/l; and Ntotal values range from 0,6 - 3 mg/l. Based on drinking water quality standards, none of the stations meet the requirements for potable water; however, the groundwater can still be used for purposes such as bathing and washing.